2012
DOI: 10.1073/pnas.1215397109
|View full text |Cite
|
Sign up to set email alerts
|

Vascular normalizing doses of antiangiogenic treatment reprogram the immunosuppressive tumor microenvironment and enhance immunotherapy

Abstract: The recent approval of a prostate cancer vaccine has renewed hope for anticancer immunotherapies. However, the immunosuppressive tumor microenvironment may limit the effectiveness of current immunotherapies. Antiangiogenic agents have the potential to modulate the tumor microenvironment and improve immunotherapy, but they often are used at high doses in the clinic to prune tumor vessels and paradoxically may compromise various therapies. Here, we demonstrate that targeting tumor vasculature with lower vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
801
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 874 publications
(829 citation statements)
references
References 36 publications
27
801
0
1
Order By: Relevance
“…While not reaching statistical significance, our data also revealed a trend toward increased CD8+ T-cell infiltration into the CNS following treatment with aflibercept, suggesting that vascular normalization could, in fact, promote immune cell infiltration. Importantly, the dose of VEGF inhibitor has been shown to modulate the level of immune cell infiltration, and may require further optimization for enhancing immunotherapeutic responses in our model [60]. Additionally, detailed characterizations of the effector functions of infiltrating immune cells, including alterations to cytotoxic function and immunosuppressive capacity, are underway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not reaching statistical significance, our data also revealed a trend toward increased CD8+ T-cell infiltration into the CNS following treatment with aflibercept, suggesting that vascular normalization could, in fact, promote immune cell infiltration. Importantly, the dose of VEGF inhibitor has been shown to modulate the level of immune cell infiltration, and may require further optimization for enhancing immunotherapeutic responses in our model [60]. Additionally, detailed characterizations of the effector functions of infiltrating immune cells, including alterations to cytotoxic function and immunosuppressive capacity, are underway.…”
Section: Discussionmentioning
confidence: 99%
“…The GL261-Quad cell line is engineered to express the model antigens human gp100 [25][26][27][28][29][30][31][32][33] , chicken OVA 257-264 , chicken OVA [323][324][325][326][327][328][329][330][331][332][333][334][335][336][337][338][339] , and mouse alloantigen I-Ea [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] . Female 6-8-week-old C57BL/6 mice (The Jackson Laboratory, Bar Harbor, ME, USA) were inoculated by stereotactic injection of 6.0×10 4 -1.0×10 5 GL261 or GL261-Quad cells into the right striatum.…”
Section: Gl261 Tumor Implantationmentioning
confidence: 99%
“…Multiple studies have demonstrated evidence of vessel normalization and increased therapeutic uptake. [22][23][24] There are also a series of studies that demonstrate the opposite effect of decreased uptake of therapeutic following anti-VEGF administration. 25 The notion that there is a therapeutic window based on dose and time likely explains these discrepant findings.…”
Section: Discussionmentioning
confidence: 99%
“…25 The notion that there is a therapeutic window based on dose and time likely explains these discrepant findings. 10,22,26 In our study, we used a relatively low human-equivalent dose of 5 mg/kg. Studies that demonstrate decreased tumor uptake of small molecule chemotherapeutics following bevacizumab administration and a lack of a survival benefit typically dose above 10 mg/ kg.…”
Section: Discussionmentioning
confidence: 99%
“…A few experimental studies have shown that endogenous T cell infiltration is increased following anti-angiogenic agents [153][154][155], and one study has shown that the efficacy of DC101 treatment is dependent on both CD4 + and CD8 + T cells in a transplantable mammary tumor model [153]. As such, the need for more investigations into the role of immunosuppressive and adaptive immune cells is warranted to help guide the future clinical possibility of combining vascular-targeting agents with immunotherapy.…”
Section: Much Less Is Known About the Role Of Tregs And T Cells Durinmentioning
confidence: 99%